Secure Dynamic Data Aggregation Routing Protocol for Wireless Sensor Networks - Mathur, Bhawana (Asian Journal of Electrical Sciences, 2012)
Routing in sensor networks is complicated due to several issues ranging from security to energy constraints of wireless sensor nodes. This distinguishes them from contemporary wireless ad hoc networks. Adversaries can launch DoS attacks by injecting false data reports via compromised nodes. Previously a Hill Climbing key dissemination filtering scheme was developed where each node disseminates its key to forwarding nodes and later transmits reports along with the key. The forwarding nodes validate the credibility of the reports based on the key obtained earlier. This approach assures stronger filtering capacity for nodes closer to data sources and achieves secure and reliable transmissions. Sensor nodes process capability, bandwidth and battery capacity is still scarce. It is necessary to save resources of sensor nodes with the purpose of prolonging network lifetime. In that regard we propose to use a dynamic data aggregation routing protocol, named DABDR along with the earlier filtering scheme for secure and dynamic transmissions in Wireless Sensor Networks.